Guinea : 2011 Article IV Consultation and Requests for a Three-Year Arrangement Under the Extended Credit Facility, and for Additional Interim Assistance Under the Enhanced Initiative for Heavily Indebted Poor Countries-Staff Report; Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for Guinea. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
This paper presents Guinea's 2011 Article IV Consultation and requests for a three-year arrangement under the Extended Credit Facility. The macroeconomic improvement in 2011 has been mainly owed to sharp fiscal adjustment. The deficit on the budget's basic balance has been reduced from 13 percent of GDP in 2010 to an estimated 2.5 percent of GDP, while monetary financing of the budget has been avoided in an effort to reduce excess liquidity stemming from large central bank advances in 2009-10. Key medium-term challenges are to reduce inflation while preparing the economy for an expected substantial increase in mining activity.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet